Effect of Trans Fatty Acid on Glucose Level and Pancreatic β Cell in Rats - Sartika, R.A.D.; Achmad, K.; Triyanti; Rustika (Pakistan Journal of Nutrition, 2016)
A high intake of trans fatty acids can cause inflammation and lipid peroxidation of cell membranes which, in turn, damage cells and tissues. The purpose of the current study was to investigate the effects of dietary trans fatty acids on blood glucose levels and pancreatic β cells. Our randomized pre-post test control group study design included two groups of Wistar rats fed either a diet containing 2% trans fat or a control diet containing no trans fat for 10 d. The results showed that blood glucose levels were not significantly different between the two groups. There was no obvious damage to pancreatic β cells, but the number of normal cells in the treatment group was less than that in control animals.